1988
DOI: 10.1111/j.0954-6820.1988.tb15883.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Results in 64 Patients Operated Upon for Pheochromocytoma

Abstract: ABSTRACT. During the years 1956–1982, 64 pheochromocytoma patients were operated upon without mortality. Twenty‐eight patients had sustained hypertension and 29 paroxysmal hypertension only. In two patients high blood pressure was not related to pheochromocytoma and five subjects were normotensive. In two women the pheochromocytoma demonstrated malignancy by widespread metastases. Sixteen patients also had neuroectodermal manifestations other than pheochromocytoma. Preoperatively, heart disease was found in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…In a Swedish cohort of 121 patients, 42 patients died during the observation period versus 23.1 expected deaths in the control population (P!0.001; Khorram-Manesh et al 2005). In a prior study performed at the same centre, however, the observed and expected mortality were similar (Stenstrom et al 1988). Our study confirms that patients with successfully resected PHEO still have a reduced life expectancy.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In a Swedish cohort of 121 patients, 42 patients died during the observation period versus 23.1 expected deaths in the control population (P!0.001; Khorram-Manesh et al 2005). In a prior study performed at the same centre, however, the observed and expected mortality were similar (Stenstrom et al 1988). Our study confirms that patients with successfully resected PHEO still have a reduced life expectancy.…”
Section: Discussionmentioning
confidence: 86%
“…Estimates of benign and malignant recurrence rate after surgery vary between 6 and 23% (Modlin et al 1979, Scott & Halter 1984, van Heerden et al 1990, Pruszczyk et al 1991, Plouin et al 1997. Conflicting results of previous cohort studies suggest that the life expectancy after PHEO surgery is either normal (Stenstrom et al 1988) or decreased (Khorram-Manesh et al 2005) when compared with the general population. Furthermore, though PHEO is generally considered to be a surgically curable cause of secondary hypertension, blood pressure remains elevated after surgery in a considerable number of patients without recurrent disease (Plouin et al 1997, Khorram-Manesh et al 2005.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…All studies were on retrospective cohorts except one on a prospective cohort (44) and one that was a randomized controlled trial (45). Of the 38 studies, 20 were performed in Europe, nine in North America, six in Asia, two in South America, and one in the Middle East.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The operative mortality at the Mayo Clinic from 1980 to 1986 was 1.3%, or 1 in 77 patients (Sheps et al, 1990). The long-term survival of patients after successful removal of a benign pheochromocytoma is essentially the same as that of age-adjusted normals and with improvement in current technique and multi-disciplinary approach, the procedure seems to be relatively safe (Stenstrom et al, 1988). …”
mentioning
confidence: 97%